To determine whether the equation \((^4√8)^{-24} \cdot (\sqrt{8})^{16} = 8^{-48}\) is true or false, let's simplify both sides.
To begin with, rewrite the terms in the left side of the equation using exponents:
- \(^4√8\) can be expressed as \(8^{1/4}\).
- \(\sqrt{8}\) can be expressed as \(8^{1/2}\).
Now, substituting these into the left side:
\[ (^4√8)^{-24} = (8^{1/4})^{-24} = 8^{-24 \cdot \frac{1}{4}} = 8^{-6} \]
\[ (\sqrt{8})^{16} = (8^{1/2})^{16} = 8^{16 \cdot \frac{1}{2}} = 8^{8} \]
Now combine these two results:
\[ 8^{-6} \cdot 8^{8} = 8^{-6 + 8} = 8^{2} \]
Now, examine the right side of the original equation:
The right side is:
\[ 8^{-48} \]
Thus we have:
\[ 8^{2} \neq 8^{-48} \]
Therefore the original equation is false.
The correct response is:
False, because the exponents should be added rather than multiplied.